(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To analyze factors associated with nurses’ compliance with postoperative patient handover using the SBAR model in the Department of Anesthesia and Pain Management, Vinmec Times City International General Hospital in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 400 postoperative handover cases from the Department of Anesthesia and Pain Management to clinical wards or between shifts. Results: Verbal SBAR compliance among nurses was five times higher when patients were hospitalized for ≥ 2 days compared to < 2 days. Nurses providing care from the second time onward were 4.5 times more likely to comply with verbal SBAR than during their first care episode. Compliance documented on the handover checklist during working hours was 0.4 times higher than that outside working hours. Conclusion: Length of hospital stay, the number of nursing care episodes, and timing of the handover are key factors influencing handover quality.